1998
DOI: 10.1152/ajpendo.1998.274.2.e238
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of thyroid hormones on the production of adrenal cAMP and corticosterone in male rats

Abstract: The acute effects of thyroid hormones on glucocorticoid secretion were studied. Venous blood samples were collected from male rats after they received intravenous 3,5,3′-triiodothyronine (T3) or thyroxine (T4). Zona fasciculata-reticularis (ZFR) cells were treated with adrenocorticotropic hormone (ACTH), T3, T4, ACTH plus T3, or ACTH plus T4 at 37°C for 2 h. Corticosterone concentrations in plasma and cell media, and also adenosine 3′,5′-cyclic monophosphate (cAMP) production in ZFR cells in the presence of 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 33 publications
0
51
0
Order By: Relevance
“…In contrast, it was reported that T3 or T4 inhibited basal and corticotropin (ACTH)-stimulated levels of intracellular cAMP in adrenal cells. 21 Incubation with T3 alone did not affect the phosphorylation level of CREB (data not shown) or CRE-dependent gene transcription ( Figure 1B) in our VSMCs. These data may suggest that cAMP level is not affected by T3 in VSMCs and the effect of thyroid hormone on cAMP level may be cell type-dependent.…”
Section: Discussionmentioning
confidence: 62%
“…In contrast, it was reported that T3 or T4 inhibited basal and corticotropin (ACTH)-stimulated levels of intracellular cAMP in adrenal cells. 21 Incubation with T3 alone did not affect the phosphorylation level of CREB (data not shown) or CRE-dependent gene transcription ( Figure 1B) in our VSMCs. These data may suggest that cAMP level is not affected by T3 in VSMCs and the effect of thyroid hormone on cAMP level may be cell type-dependent.…”
Section: Discussionmentioning
confidence: 62%
“…One possibility includes a PRLinduced promotion of adrenal steroidogenesis. It is well known that ACTH regulates glucocorticoid secretion through the cyclic AMP (cAMP) pathway [31][32][33][34][35][36][37]. It has been shown that the action of PRL might be mediated through G-protein-adenylate cyclase coupling and cAMP production [38,39], where in chronic hyperprolactinemia enhances receptor-G-protein-adenylate cyclase coupling and cAMP production [2].…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects have been found for PRL o n s e c r e t i o n o f a l d o s t e r o n e , c o r t i s o l , d e h y d r o e p i a n d r o s t e r o n e ( D H E A ) a n d / o r dehydroepiandrosterone sulfate (DHEAS) in human and nonhuman primate adrenals [11, 19- 22]. Moreover, PRL increase in vitro secretion of corticosterone and aldosterone in rat adrenocortical cells [4,[23][24][25][26][27]. In the present study, PRL stimulation of adrenal steroid release was found to be dependent on Jak2 activity since PRL-induced adrenal steroid release was significantly prevented by AG490.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that a PRL induced promotion of adrenal steroidogenesis. It is well known that ACTH regulates glucocorticoid secretion through the cyclic AMP (cAMP) pathway [25,26,[30][31][32][33][34]. Furthermore, adrenal steroidogenic enzymes, including a number of cytochrome P450 family and hydroxysteroid dehydrogenase (HSD) family members, and steroidogenic proteins, such as steroidogenic acute regulatory protein (StAR) and peripheral benzodiazepine binding receptor (PBR), are controlled by ACTH mainly through the cAMP signaling pathway.…”
Section: Discussionmentioning
confidence: 99%